Synthesis and optimization of MoS2@Fe3O4-ICG/Pt(IV) nanoflowers for MR/IR/PA bioimaging and combined PTT/PDT/Chemotherapy triggered by 808 nm laser - Liu, Bei (2019)
Elaborately designed biocompatible nanoplatforms simultaneously achieving multimodal bioimaging and therapeutic functions are highly desirable for modern biomedical applications. Herein, uniform MoS2 nanoflowers with a broad size range of 80–180 nm have been synthesized through a facile, controllable, and scalable hydrothermal method. The strong absorbance of MoS2 nanoflowers at 808 nm imparts them with high efficiency and stability of photothermal conversion. Then a novel multifunctional composite of MoS2@Fe3O4‐ICG/Pt(IV) (labeled as Mo@Fe‐ICG/Pt) is designed by covalently grafting Fe3O4 nanoparticles with polyethylenimine (PEI) functionalized MoS2, and then loading indocyanine green molecules (ICG, photosensitizers) and platinum (IV) prodrugs (labeled as Pt(IV) prodrugs) on the surface of MoS2@Fe3O4. The resulting Mo@Fe‐ICG/Pt nanocomposites can achieve excellent magnetic resonance/infrared thermal/photoacoustic trimodal biomaging as well as remarkably enhanced antitumor efficacy of combined photothermal therapy, photodynamic therapy, and chemotherapy triggered by a single 808 nm NIR laser, thus leading to an ideal nanoplatform for cancer diagnosis and treatment in future.